Metallophthalocyanines Bearing Polymerizable {[5-({(1E)-[4-(Diethylamino)phenyl]methylene}amino)-1-naphthy1]oxy} Groups as Electrochemical Pesticide Sensor - KOCA, ATIF (WILEY-V C H VERLAG GMBH, 2017)
The synthesis and characterization of novel metallophthalocyanines (MPcs(ea)) carrying {[5-({(1E)-[4-(diethylamino)phenyl]methylene}amino)-1-naphthyl]oxy} groups on four peripheral positions have been reported. These complexes have been characterized by a combination of FT-IR, H-1 and C-13 NMR, mass and UV-Vis spectroscopy techniques. Redox active metal centers in the core of the Pc rings (Co (II) [CoPc(ea)], Mn(III) [Cl-MnPc(ea)], and Ti(IV)O [TiOPc(ea)]) and electropolymerizable substituents on the peripheral positions of Pc rings were used to increase redox activity and electrochemically polymerization ability of the complexes. The redox properties of MPcs(ea) were determined with voltammetry and insitu spectroelectrochemistry techniques. Then, GCE/MPc(ea) electrodes were constructed with the electropolymerization of MPcs and these electrodes were tested as the pesticide sensors. Sensing studies indicated that type of the metal center of the complexes effectively influenced the sensing activities. While all complexes showed interaction abilities for the fenitrothion, parathion and eserine, GCE/CoPc(ea) electrode detected the parathion selectively with LOD value of 4.52x10(-7)moldm(-3) among studied three pesticides. Moreover, GCE/MnClPc(ea) electrode selectively detected eserine with LOD value of 6.43x10(-7)moldm(-3) and GCE/TiOPc(ea) electrode detected parathion with LOD value of 8.64x10(-7)moldm(-3). All GCE/MPcs(ea) electrodes showed high sensitivity and wide linear ranges for those pesticides. These sensing data illustrated the usability of these modified electrodes in real samples such as seawater with good selectivity and sensitivity.
Keywords: Electrochemistry; Electropolymerization; Selective pesticide sensor; Metallophthalocyanine; Modified electrode; REDUCED GRAPHENE OXIDE; PHTHALOCYANINE COMPLEXES; SPECTROELECTROCHEMICAL PROPERTIES; CO(II) PHTHALOCYANINES; AXIAL COORDINATION; MANGANESE; ELECTRODE; FENITROTHION; COBALT; PROBE